Mitochondrial SNP markers to monitor evolutionary lineage ancestry in Apis mellifera mellifera conservation programs - Henriques, Dora (2018)
The European dark honey bee, Apis mellifera mellifera , is threatened inmost of its native range, in part, due to introgressive hybridization with bees from the highly divergent C-lineage, mainly Apis mellifera carnica and Apis mellifera ligustica (De la Rúa et al. 2009; Pinto et al. 2014). Yet, the maintenance of locally adapted genetic diversity is critical for the population long-term survival and sustainability (De la Rúa et al. 2009; Meixner 2010). The growing awareness that genetic diversity is important for sustainable beekeeping led to implementation of different conservation and breeding programs throughout Europe, which are in need of reliable and costefficient molecular tools to accurately monitor Clineage introgression into A. m. mellifera (De la Rúa et al. 2009; Henriques et al. 2018a, b; Meixner 2010). The large mating flight distances and the polyandrous mating system make it challenging to preserve honey bee subspecies in an open conservation area where intruders can fly in (Neumann et al. 1999). It is therefore necessary to regularly control the genetic ancestry of new or superseded colonies.